1963
DOI: 10.5254/1.3539593
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption of Elastomers

Abstract: This study considers high temperature (160° C) water absorption in the absence of oxygen. Examination of the freezing behavior of water-swollen butyl gum vulcanizates shows the water to be disposed as discrete droplets of the order of 3µ diameter, corresponding in this case with soluble residues based on zinc. Data are shown for peroxide gum vulcanizates of natural rubber, SBR, NBR, ethylene-propylene rubber, and cis-1,4 poly butadiene. Equilibrium absorption occurs, the degree being dependent on polymer impur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The values of CLD thus obtained will give different results partly because of the time scale of the measurements 6. Because of the equilibrium nature of swelling measurements, the value of CLD will have lower contributions from the entanglements, as the time scale of the experiment permits disentanglement of temporary entanglements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of CLD thus obtained will give different results partly because of the time scale of the measurements 6. Because of the equilibrium nature of swelling measurements, the value of CLD will have lower contributions from the entanglements, as the time scale of the experiment permits disentanglement of temporary entanglements.…”
Section: Methodsmentioning
confidence: 99%
“…Bahar et al5 gave a detailed study of the swelling of butadiene elastomers of different crosslink densities with finely divided sodium chloride (NaCl) particles in water, water/acetone, and water/THF mixtures. Briggs et al6 and Edwards7 reported absorption of water by butyl elastomers. They observed that crosslinked butyl elastomers absorbed significant amount of water when small amount of salts were added to the samples during crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomena of sorption and diffusion in aliphatic polyamides have received considerable attention [1][2][3][4] . Numerous studies have been done on diffusion of water in polymers 5 and the basic mechanism of water absorption in rubber vulcanizates containing hydrophilic impurities is known 6,7 . Studies on moisture sorption and diffusion in crystalline materials, such as aromatic polyamide fibres with rigid and extended chain conformation, are available [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…He reports G values of 2.2 and 4.8 fbr the chain scission and crosslinking processes, respectively. BRIGGS et al 7) have studied the deformation under applied pressure of a number of ethylene/propylene elastomers after irradiation in vacuo. KARPOV and coworkers@ reported an increased crosslinking efficiency when irradiation of ethylene/propylene copolymer is carried out in the presence of nitrous oxide.…”
Section: A Introductionmentioning
confidence: 99%